Analyse linguistique d'un corpus épistolaire en moyen arabe: Les lettres luso-marocaines conservées aux archives nationales de la Torre do Tombo. - Guerrero, Jairo (Arabica, 2023)
In this paper we provide a linguistic analysis of a recently digitized Luso-Moroccan correspondence corpus kept in the Portuguese National Archives of Torre do Tombo. All these documents date back to the first half of the tenth/sixteenth century and stand out for their being written in Middle Arabic, a language register which is characterized by the use of features from both classical and colloquial Arabic. The ultimate aim of this study is to find some clue to enable us to trace the history of present-day Moroccan Arabic dialects.